Employee Temperament As A Predictor of Workstress among Plant Turnaround Workers - Alhassan Musah, Adiza.; Ghazali, Zulkipli,; Nizam. ShahrulIsha, Ahmad, (International Journal of Psychosocial Rehabilitation, 2020)
Temperaments can play either a strong or a weak role in work stress. This study aims to examine the effects of the four temperaments on work-related stress among plant turnaround maintenance employees. Temperament was assessed by the Temperament Inventory (TI), and work stress was assessed using questions relevant to the plant turnaround maintenance work environment. Structural equation modeling was used to test the hypotheses. Findings revealed that whereas a sanguine temperament played a defensive effect on stress, choleric and phlegmatic temperaments are both susceptible to more stress. However, melancholic temperament, alternatively, showed a hyper-adaptive effect in stressful situations. The results of this study suggest that it would be beneficial for employees with choleric and phlegmatic temperaments to be identified due to their high susceptibility, as they are likely to suffer high levels of stress. This study argues that understanding, identifying, and recognizing individual genetic disposition and dispositional-related stressors by management and colleagues would help to improve the delivery of collegial and organizational-level support.